2017
DOI: 10.1071/mf16296
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the movement patterns of false killer whales (Pseudorca crassidens) in coastal and pelagic waters of the Northern Territory, Australia

Abstract: The false killer whale (Pseudorca crassidens) is regarded as Data Deficient globally and in Australia. In most parts of its range, there is little information on its social behaviour, dispersal or ecology. The present study is the first assessment of its movement patterns in Australian waters, on the basis of satellite tracking of four individuals, in the Arafura and Timor Seas from late March to early July 2014. When initially tagged, the four individuals occurred in a single group; they then showed generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Currently, there is little basis for understanding coastal dolphin movement and ranging patterns in monsoonal northern Australia. Coastal dolphins may be responding to seasonal influences (Smith, 2012;Palmer et al, 2017) and spatial and temporal variation in the abundance of prey species (Silva et al, 2009;Cagnazzi et al, 2013;Parra and Cagnazzi, 2016). However, the results have highlighted that the study period (three and half years) and study area (1086 km 2 ) didn't encompass the whole ranging patterns for the three species, which appears to be much larger than assumed (Silva et al, 2009;Nicholson et al, 2012;Palmer et al, 2014b;Brown et al, 2016).…”
Section: Monitoring Variation and Abundance Estimatesmentioning
confidence: 77%
“…Currently, there is little basis for understanding coastal dolphin movement and ranging patterns in monsoonal northern Australia. Coastal dolphins may be responding to seasonal influences (Smith, 2012;Palmer et al, 2017) and spatial and temporal variation in the abundance of prey species (Silva et al, 2009;Cagnazzi et al, 2013;Parra and Cagnazzi, 2016). However, the results have highlighted that the study period (three and half years) and study area (1086 km 2 ) didn't encompass the whole ranging patterns for the three species, which appears to be much larger than assumed (Silva et al, 2009;Nicholson et al, 2012;Palmer et al, 2014b;Brown et al, 2016).…”
Section: Monitoring Variation and Abundance Estimatesmentioning
confidence: 77%
“…There are some significant deep channels on the eastern side (<164 m), and large tides (<8 m) [37] combined with seasonal monsoons, in which wind strength and direction change [38], which may interfere with animal movements, perhaps through the avoidance of rough surface currents flowing against them when travelling at sea. Satellite tracking of false killer whales ( Pseudorca crassidens ) in the Cobourg Peninsula area has shown that they rarely entered the western side of the Cobourg Peninsula, into Van Diemen Gulf, despite occupying shallow (<10 m depth) waters within 10km of the coast, on the eastern side [39], which could also be related to currents.…”
Section: Discussionmentioning
confidence: 99%
“…Such capability is supported by the total distance travelled and/or the continuous movements monitored via satellite-linked telemetry in short-finned pilot whales off Florida (Well et al 2013) and Hawai'i (Abecassis et al 2015), as well as in other delphinid species. Examples include the related congener species, the long-finned pilot whale (G. melas) (Nawojchik et al 2003), the false killer whale (Pseudorca crassidens) (Baird et al 2012;Palmer et al 2017), the pigmy killer whale (Feresa attenuata) (Baird et al 2011), or the killer whale (Dahlheim et al 2008;Durban and Pitman 2012). Yet, none of the previous examples relate to animals with (known strong) site fidelity, contrary to what shown in our study.…”
Section: Discussionmentioning
confidence: 99%